Electrochemically Driven Coordination Tuning of FeOOH Integrated on Carbon Fiber Paper for Enhanced Oxygen Evolution. Issue 18 (8th April 2019) - Han, Xiaotong; Yu, Chang; Yang, Juan; Song, Xuedan; Zhao, Changtai; Li, Shaofeng; Zhang, Yan; Huang, Huawei; Liu, Zhibin; Huang, Hongling; Tan, Xinyi; Qiu, Jieshan
Abstract: Coordination tuning of catalysts is a highly effective strategy for activating and improving the intrinsic activity. Herein, a Co‐engineered FeOOH catalyst integrated on carbon fiber paper (Co‐FeOOH/CFP) is reported, which realized a great improvement of the oxygen evolution activity by tuning the coordination geometry of the Fe species with an electrochemically driven method. Experiments and theoretical calculation demonstrate that the FeO bonds of FeOOH are partially broken, which is rooted in the Co incorporation, thus resulting in unsaturated FeO6 ligand structures and a relatively narrow bandgap. Consequently, the reorganized Fe sites on the surface show an enhanced capability for adsorbing OH − species and the Co‐FeOOH exhibits an improved conductivity. As expected, the Co‐FeOOH/CFP hybrids exhibit an extremely low overpotential of ≈250 mV at 10 mA cm −2 and a small Tafel slope, which far outperforms that of electrochemically sluggish FeOOH. The present work emphasizes the importance of local Fe coordination in catalysis and provides an in‐depth insight into the mechanism of the enhanced catalytic activity. Abstract : Cobalt engineered FeOOH with super‐enhanced conductivity and activity is configured via an electrochemically driven coordination tuning strategy to overcome the insulative property of FeOOH. Benefiting from the unsaturated FeO6 ligand structures that are rooted in the Co incorporation, the reorganized Fe sites of Co‐FeOOH show enhanced capability for adsorbing OH − species and superb electrochemical activity, indicative of Co modulated and super‐activated behavior.